URDU- CAUSES AND EFFECTS OF ATHEISM GROWING IN THE NEW GENERATION: CRITICISM AND ANALYSIS - Muhammad Shahbaz Manj; Muhammad Shahbaz (دی اسکالر)
Atheism is an important term used in Islamic texts to refer to those who do not believe in God. The reason for using it in the sense of deviation is that the word is derived from the Arabic word lahad which is used for the crack in the grave which separates or deviates from the middle. In Islamic terminology, the word atheist refers to those who deny the existence of God altogether - those who practice atheism are also called atheists, atheists, materialists, or atheists. The number of atheists is one billion atheists and agnostics worldwide, according to sociologist Ariela Keysar's numerous international studies on atheism and a review by Juhem Navarro Rivera. And it makes up 7% of the world's population. China has the largest number of atheists in the world at 400 million. According to atheists, "the world was not created by any god, but came into being by itself, or it already existed and will continue to exist in various forms over time."